2020
DOI: 10.1016/j.eclinm.2019.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of health behaviour change intervention through women's self-help groups on maternal and newborn health practices and related inequalities in rural india: A quasi-experimental study

Abstract: a b s t r a c tBackground: Despite the health system effort s, health disparities exist across sub-populations in India. We assessed the effects of health behaviour change interventions through women's self-help groups (SHGs) on maternal and newborn health (MNH) behaviours and socio-economic inequalities. Methods: We did a quasi-experimental study of a large-scale SHG program in Uttar Pradesh, India, where 120 geographic blocks received, and 83 blocks did not receive health intervention. Data comes from two cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
154
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(167 citation statements)
references
References 25 publications
11
154
0
Order By: Relevance
“…The SHG platform is the underlying developmental model of the IMFHL program evaluated in this paper. The IMFHL program aimed to empower marginalised women by organising them in self-help groups comprising 10-15 households to adopt desired health behaviours and provide access credit for poverty reduction (44,45). Studies have shown that SHG membership fosters social capital and cohesion among member through group collectivisation, with membership in uencing social norms and behaviours (39,40,41).…”
Section: Community-based Health Literacy and Micro Nance Programmentioning
confidence: 99%
See 4 more Smart Citations
“…The SHG platform is the underlying developmental model of the IMFHL program evaluated in this paper. The IMFHL program aimed to empower marginalised women by organising them in self-help groups comprising 10-15 households to adopt desired health behaviours and provide access credit for poverty reduction (44,45). Studies have shown that SHG membership fosters social capital and cohesion among member through group collectivisation, with membership in uencing social norms and behaviours (39,40,41).…”
Section: Community-based Health Literacy and Micro Nance Programmentioning
confidence: 99%
“…While most studies attribute the change in health behaviours due to the in uence of program input, limited studies have explored the phenomenon of diffusion of health literacy from program members to non-members (44,39,46). Diffusion in this paper adopts a de nition that explains the process by which an innovation -in this case, the knowledge of maternal danger signs, is communicated through programmatic channels over time from members to non-members of a social system (43).…”
Section: Community-based Health Literacy and Micro Nance Programmentioning
confidence: 99%
See 3 more Smart Citations